HISTORISITAS DAN FORMULASI KALENDER BILANG TAUNG BUGIS PERSPEKTIF ILMU FALAK: Indonesia - Nur Lela; Agus, Jasdar; Mustafa, Adriana (Universitas Islam Negeri Alauddin Makassar, 2024)
This article discusses the historicity and formulation of the said taung Bugis calendar from the perspective of falak. The main problem in this study is how is the historicity and formulation of the said taung Bugis calendar from the perspective of falak, which is described into several problem formulations: 1) What is the history of the Said Taung Bugis calendar?, 2) How is the formulation of the Said Taung Bugis calendar from the perspective of science?. The objectives of this study are: 1) To find out the history of the Bilang Taung Bugis calendar, 2) To find out the formulation of the Said Taung Bugis calendar from the perspective of science. The Bilang Taung Bugis calendar as a dating system of the Bugis people comes from an ancient manuscript called Lontara Katakan. This calendar has a number of days as many as 365 days that use the same solar circulation system as the Gregorian calendar. The beginning of the year of this calendar begins on May 16 in the Gregorian calendar or 1 Sarawanai in the Bugis calendar. The calculation made in making the conversion is based on the conversion analysis of the Bugis-Makassar Calendar and the Gregorian Calendar by Muh. Fadil Student of UIN Walisongo Semarang. The calculation is taken from the beginning of each month in the Bugis calendar, starting from the month of Sarawanai to the month of Jettai. The Bilang Taung Bugis calendar besides being used by the Bugis tribe is also used by the Makassar tribe. The names in this calendar include: Sarawanai, Padawaranai, Sujiari, Pacingkai, Posiyai, Mangasirai, Magasettiwi, Mangalompai, Nagai, Palagunai, Biasakai, and Jettai. The implementation of this calendar can be applied to convert the calendar to the Gregorian and Hijri calendars. The presence of this research is expected to make a major contribution in efforts to preserve local wisdom owned by the Bugis community. Keywords: Historicity, Formulation, Calendar Bilang Taung, Science Falak